PENGARUH PERFORMANCE KARYAWAN DAN KUALITAS PRODUK MAKANAN TERHADAP KEPUASAN PELANGGAN DI PT SURYA TANJUNG JAYA - Syaifullah (Journal of Social Sustainability Management, 2021)
Study of this research is the influence of Peformance Employee and Product Quality to Customer Satisfaction at PT Surya Tanjung Jaya. The object of this research is all customers of PT Surya Tanjung Jaya. While the purpose of this study is to determine whether there is partial or simultaneous influence between the Employee's Performance and Product Quality to Customer Satisfaction. Sampling technique using saturated sampling method, total sample or also called census method that is by making the entire population as sample, total population which is taken as sample is 125 consumer. The data The analysis technique used is multiple linear regression analysis. Based on the result of research known that t test result where t count for Employee's Performance = 6,495> t table (1,9796) and t count for Product Quality variable = 6,522> t table (1,9796). So it can be concluded partially there is a positive and significant influence of Employee Performance (X1) on Customer satisfaction variable (Y), there is a positive and significant influence of Product Quality (X2) on customer satisfaction variables (Y). F test results where F arithmetic 101.506> F table (3.070). were collected using questionnaire method using Likert scale. Then it can be concluded that simultaneously there is a positive and significant influence of Employee Performance (X1) and Product Quality (X2) variable to customer satisfaction variables (Y).